(untitled) (Journal of Shaheed Suhrawardy Medical College, 2018)
Intrauterine insemination (IUI) is the therapeutic process of placing washed spermatozoa transcervically into the uterine cavity for the treatment of infertility. IUI theoretically allows a relatively higher number of motile spermatozoa to reach the oocyte. This study is a cross sectional prospective study done on 52 cases in newly started Dhaka Medical College Hospital Fertility Care Centre from October 2015 to March 2016. Among the 52 cases 4 cases became pregnant by IUI (7.7%) which is equivalent to the success rate observed in other established centers. The outcome suggests that IUI is possible in a relatively new center with limited technology setting. It may be considered as a good treatment option for couples with unexplained infertility, male factor infertility, and anovulation related infertility. Further improvement of this infertility center can bring better outcome in the treatment of infertility in the public sector. J Shaheed Suhrawardy Med Coll, December 2016, Vol.8(2); 49-53